ln(4x+5)=ln(2x-1)+ln(3)

Simple and best practice solution for ln(4x+5)=ln(2x-1)+ln(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(4x+5)=ln(2x-1)+ln(3) equation:


Simplifying
ln(4x + 5) = ln(2x + -1) + ln(3)

Reorder the terms:
ln(5 + 4x) = ln(2x + -1) + ln(3)
(5 * ln + 4x * ln) = ln(2x + -1) + ln(3)
(5ln + 4lnx) = ln(2x + -1) + ln(3)

Reorder the terms:
5ln + 4lnx = ln(-1 + 2x) + ln(3)
5ln + 4lnx = (-1 * ln + 2x * ln) + ln(3)
5ln + 4lnx = (-1ln + 2lnx) + ln(3)

Reorder the terms for easier multiplication:
5ln + 4lnx = -1ln + 2lnx + 3ln

Reorder the terms:
5ln + 4lnx = -1ln + 3ln + 2lnx

Combine like terms: -1ln + 3ln = 2ln
5ln + 4lnx = 2ln + 2lnx

Solving
5ln + 4lnx = 2ln + 2lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-2ln' to each side of the equation.
5ln + -2ln + 4lnx = 2ln + -2ln + 2lnx

Combine like terms: 5ln + -2ln = 3ln
3ln + 4lnx = 2ln + -2ln + 2lnx

Combine like terms: 2ln + -2ln = 0
3ln + 4lnx = 0 + 2lnx
3ln + 4lnx = 2lnx

Add '-2lnx' to each side of the equation.
3ln + 4lnx + -2lnx = 2lnx + -2lnx

Combine like terms: 4lnx + -2lnx = 2lnx
3ln + 2lnx = 2lnx + -2lnx

Combine like terms: 2lnx + -2lnx = 0
3ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(3 + 2x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Add '-2x' to each side of the equation. 2x + -2x = -3 + -2x Combine like terms: 2x + -2x = 0 0 = -3 + -2x Simplifying 0 = -3 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x+(x+1)+(x+2)+(x+3)=66 | | 2x+96-0= | | 4y+3=14 | | 38x+5y= | | 4y+4x-xy=0 | | 2p^2-2p/7p-7= | | Sqrt[x]=30 | | x-4y-12=0 | | dx+x(lnx-lny-1)dy=0 | | x^2-2x=-1/2 | | 3x+3y=132 | | 20x-(7x-8)=47 | | -(5a+6)=-2(3a+8) | | x-0.25x=22.50 | | 4x^3-6x^2-72x+48=0 | | 10a^4b^2/15a^2b^3c^2 | | 9x+25= | | 394/2000 | | (2x+1)*2x=20 | | 2x(2x^2+24x+27)=0 | | 3x+4x-5x+6=0 | | Ln(x)-2x=0 | | ln(x)=2x | | lnx=2x | | 7x+8x-3x+6=0 | | -3x+5x=18 | | 25-5/17 | | 3x(2-x)-5(6-2x)=0 | | 13/5/5 | | 0.07m=0.4x | | 13/5//5 | | 1/5(x=2=-3 |

Equations solver categories